Variable Response to Propranolol Treatment of Kaposiform Hemangioendothelioma, Tufted Angioma, and Kasabach-Merritt Phenomenon - Chiu, Yvonne E. (2012)
Propranolol is a non-selective beta-adrenergic antagonist successfully used in a case of kaposiform hemangioendothelioma associated with Kasabach-Merritt phenomenon. We report eleven patients treated with propranolol for kaposiform hemangioendothelioma and the related variant tufted angioma, six of whom also had Kasabach-Merritt phenomenon. The varied responses to treatment, with only 36% responding in our series, demonstrate the need for further study of this medication before routine use for these indications.